Analysis of the Application of Differentiated Learning in High School Biology Lessons: Analisis Penerapan Pembelajaran Berdiferensiasi Pada Pelajaran Biologi SMA - Putra, Muhammad Rizky Pratama; Salsabila, Najla Dwi; Sari, Indah Juwita (Jurusan Pendidikan Biologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Timor, 2025)
The times and needs of students require adjustments in the education system. The Merdeka Curriculum is a way out of this problem by providing space for students to learn according to their interests and learning styles. In its implementation, differentiated learning is the main approach which aims to create a fun and meaningful learning experience, especially in essential material such as biology. This research aims to determine the application of differentiated learning in biology lessons at the high school level. Using descriptive qualitative methods, the research was conducted from October to November 2024 involving several biology teachers at Banten Province High Schools as samples. Data was collected through structured interviews based on instruments prepared in accordance with the research objectives. The research results show that differentiated learning has been implemented by adapting learning models and methods to student characteristics. This differentiation approach has a positive impact on teachers and students, such as increasing student activity and more effective understanding of the material and freedom for teachers to adjust learning. However, its effectiveness is highly dependent on student motivation and the challenges teachers face, both from internal and external classroom factors. Therefore, evaluation is the key to improving the quality of learning for better education in the future.